2005
DOI: 10.1897/04-251r1.1
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive, physiological, and biochemical responses in juvenile female rainbow trout (oncorhynchus mykiss) exposed to sediment from pulp and paper mill industrial discharge areas

Abstract: Four pulp and paper mills discharge their effluents in the same section of the Biobio River in central southern Chile. Pulp mill effluents are a very complex mixture with characteristics that depend on the type of raw material, the process technology, and the effluent treatment. To investigate the effect of pulp mill effluent discharges, immature Oncorhynchus mykiss were exposed to river sediments in the laboratory for 29 d. Three sampling areas were defined in a spatial gradient in the river: Preimpact, impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 49 publications
7
56
1
2
Order By: Relevance
“…In the early stages of gonad maturation, steroid hormones work in a positive feedback mechanism to increase VTG concentrations in the blood. However, during the later maturation stages, steroids are regulated via negative feedback loops causing decreases in blood VTG [8]. By comparison, sample 9 had the highest VTG plasma concentration in the female group, but had the lowest female GSI and the majority oocytes were in immature stages I and II.…”
Section: Relating Gsi Plasma Vtg and Gonad Developmentmentioning
confidence: 94%
See 2 more Smart Citations
“…In the early stages of gonad maturation, steroid hormones work in a positive feedback mechanism to increase VTG concentrations in the blood. However, during the later maturation stages, steroids are regulated via negative feedback loops causing decreases in blood VTG [8]. By comparison, sample 9 had the highest VTG plasma concentration in the female group, but had the lowest female GSI and the majority oocytes were in immature stages I and II.…”
Section: Relating Gsi Plasma Vtg and Gonad Developmentmentioning
confidence: 94%
“…VTG content was determined using a previously described ELISA protocol using a 96 well flat bottom, half volume, and high binding polystyrene plate [8]. The plate was incubated with rainbow trout VTG (Biosense Laboratories™, Bergen, Norway) as the standard, and the trout plasma samples.…”
Section: Blood Plasma Protein Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, other inputs of vascular plant phytosterols into coastal waters may come from upland forests, mangroves, oil palm, or coconut plantations (Ali et al, 2009), waste waters (Quemeneur & Marty, 1994;Liu et al, 2010) and the pulp and paper mill industry (Owens, 1991;Sepúlveda et al, 2003;Orrego et al, 2005aOrrego et al, , 2009). Important research efforts has been undertaken to evaluate the impact of the discharge of pulp mill effluents on fish reproductive behavior (e.g., Walker et al, 2002;Dubé et al, 2008), because it has been shown that fishes exposed to wood-derived sterols present endocrine disruption (Mellanen et al, 1996;MacLatchy et al, 1997;Nakari & Erkomaa, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Bertin et al (2011) recently showed remarkably high levels of 17α-ethinylestradiol in coastal sediments, enough to cause endocrine disorders in fish inhabiting some of the aquatic ecosystems of this region. In addition, several studies have shown endocrine-disrupting effects in caged rainbow trout located downstream from pulp mill discharges in the BioBío River (Orrego et al, 2005a(Orrego et al, , 2006(Orrego et al, , 2009. There is an important production of cellulose in south-central Chile of about 3.32 million ton annually; accordingly, phytosterols derived from this activity are incorporated into aquatic systems.…”
Section: Introductionmentioning
confidence: 99%